A chemometric approach to evaluate the impact of pulses, Chlorella and Spirulina on proximate composition, amino acid, and physicochemical properties of turkey burgers. (27th February 2019) - Marti‐Quijal, Francisco J; Zamuz, Sol; Tomašević, Igor; Rocchetti, Gabriele; Lucini, Luigi; Marszałek, Krystian; Barba, Francisco J; Lorenzo, José M
Abstract: BACKGROUND: Changes in physicochemical parameters, proximate composition, amino acid and taste profiles of turkey burgers enriched by 1% with soy (control), pulses, Chlorella and Spirulina proteins were studied. RESULTS: Color parameters, pH, ash content, total, essential and non‐essential amino acids were significantly different among the different types of turkey burgers prepared. In this regard, turkey burgers made with pea protein presented the highest values for pH and lightness, whereas the samples prepared with broad bean showed the highest redness. The inclusion of bean and seaweed produced a marked increase of glutamic acid, lysine and aspartic acid. However, the taste profile was similar in the different six turkey burgers studied (soy, pea, lentil, broad bean, Chlorella and Spirulina protein). Orthogonal projections to latent structures discriminant analysis (OPLS‐DA) allowed to classify turkey burgers according to protein sources, as compared to soy (control). Textural parameters, moisture and color were found to be the most discriminant parameters, able to describe the differences among burgers. Nonetheless, according to the supervised OPLS model, broad beans were found to possess a similar profile to soy (control). CONCLUSION: Considering all studied parameters, the enrichment of turkey burgers with bean proteins could be used as a promising alternative to soy proteins from a technological point of view. © 2019 Society of Chemical Industry